Three new species of Lithophane Hübner (Lepidoptera: Noctuidae: Xyleninae) - Troubridge, J. T. (Zootaxa, 2006)
Three new species of Lithophane Hübner are described: Lithophane lanei and L. scottae from eastern Ontario, Canada, and L. boogeri from the high desert of Oregon, U.S.A. Adults and genitalia are illustrated.